A task-sharing intervention for prepartum common mental disorders: Feasibility, acceptability and responses in a South African sample - Spedding, M.; Stein, D.J.; Naledi, T.; Myers-Franchi, Bronwyn; Cuijpers, P.; Sorsdahl, K.R. (2020)
Background: Peripartum common mental disorders (CMD) are highly prevalent in low- and middle-income countries (LMIC) such as South Africa. With limited public mental health resources, task sharing approaches to treatment are showing promise. However, little is known about the feasibility and acceptability of, as well as responses associated with problem-solving therapy (PST) for the treatment of prepartum CMD symptoms in South African public health settings.